I International Congress: Western Esotericism in and from Latin America - Tamayo, Carolina (2022)
I International Congress: Western Esotericism in and from Latin America, 10th Anniversary of the Center for Studies on Western Esotericism UNASUR, the Journal of Melancholy History of CEEO-UNASUR, the Institute of Ancient and Medieval History and the Research Project “FILOCyT19055: Esotericism and power in early modernity ”of the University of Buenos Aires, the Institute of Philological Research of the National Autonomous University of Mexico, the Department of Letters and the Research Group“ Hermaïkos Herméticos Estudos ”of the Federal University of Pernambuco, the Group of Research "Arts and Thought Models" of the University of Antioquia, the Coordination of International Affairs and the REHMLAC +, Journal of Historical Studies of Latin American and Caribbean Freemasonry plus of the Pacific Headquarters and the School of General Studies of the University of Costa Rica, and the Center for Social and Human Sciences of the Federal University of Santa Maria, VI-UCR no . 1045, August 9-11, 2021. https://www.youtube.com/playlist?list=PLtTONsUaNQcID_Akxt4Kix3tAmCGILpHW